$$$a_1 = 1$$$
$$$a_2 = 5$$$
$$$a_n = a_{n-1} + n^2(a_{n-2}+1)$$$
Prove $$$a_n=(n+1)!-1$$$
P.S. Original problem
# | User | Rating |
---|---|---|
1 | tourist | 3856 |
2 | jiangly | 3747 |
3 | orzdevinwang | 3706 |
4 | jqdai0815 | 3682 |
5 | ksun48 | 3591 |
6 | gamegame | 3477 |
7 | Benq | 3468 |
8 | Radewoosh | 3462 |
9 | ecnerwala | 3451 |
10 | heuristica | 3431 |
# | User | Contrib. |
---|---|---|
1 | cry | 168 |
2 | -is-this-fft- | 162 |
3 | Dominater069 | 160 |
4 | Um_nik | 159 |
5 | atcoder_official | 156 |
6 | adamant | 153 |
6 | djm03178 | 153 |
8 | luogu_official | 149 |
9 | awoo | 147 |
10 | TheScrasse | 146 |
[SOLVED] How to prove reduction of this induction to formula?
$$$a_1 = 1$$$
$$$a_2 = 5$$$
$$$a_n = a_{n-1} + n^2(a_{n-2}+1)$$$
Prove $$$a_n=(n+1)!-1$$$
P.S. Original problem
Name |
---|